2017
DOI: 10.1136/gutjnl-2017-313942
|View full text |Cite
|
Sign up to set email alerts
|

Differential preventive activity of sulindac and atorvastatin in Apc+/Min-FCCCmice with or without colorectal adenomas

Abstract: ObjectiveThe response of subjects to preventive intervention is heterogeneous. The goal of this study was to determine if the efficacy of a chemopreventive agent differs in non-tumour-bearing animals versus those with colorectal tumours. Sulindac and/or atorvastatin was administered to Apc+/Min-FCCC mice with known tumour-bearing status at treatment initiation.DesignMale mice (6–8 weeks old) underwent colonoscopy and received control chow or chow with sulindac (300 ppm), atorvastatin (100 ppm) or sulindac/ator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
3
28
0
1
Order By: Relevance
“…Furthermore, we believe the question of relative contribution of COX-1 and COX-2 activity to the PGE 2 formation to be critical for the assessment of aspirin's anti-tumor effect in different stages of prevention, i.e., in the context of normal noninflamed mucosa (as in this study), or in the context of adenoma progression toward colorectal carcinoma. In this regard, recent observations in an established murine CRC model impressively revealed the significance of the tumor status on the time of treatment initiation for the efficacy of chemopreventive agents against adenoma formation (60).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we believe the question of relative contribution of COX-1 and COX-2 activity to the PGE 2 formation to be critical for the assessment of aspirin's anti-tumor effect in different stages of prevention, i.e., in the context of normal noninflamed mucosa (as in this study), or in the context of adenoma progression toward colorectal carcinoma. In this regard, recent observations in an established murine CRC model impressively revealed the significance of the tumor status on the time of treatment initiation for the efficacy of chemopreventive agents against adenoma formation (60).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination failed to inhibit progression in those with advanced adenomas or colon cancer. A clinical assessment of the NSAID/statin duo in combination with a chemotherapeutic agent has not yet been conducted in humans but has shown promise in animal models [57].…”
Section: Modifiable Risk Factorsmentioning
confidence: 99%
“…Certain medications that are commonly prescribed for other conditions, such as NSAIDs, statins, and bisphosphonates have been shown to protect against CRC, especially when used in combination. These compounds may also facilitate the treatment of CRC in combination with chemotherapeutic agents [5760]. However, due to the limited data available and possible side-effects, these medications are not recommended to the general public simply for the prevention of CRC.…”
Section: Preventionmentioning
confidence: 99%
“…Clinical studies have shown that the loss of RPRM expression is as common event in gastric cancer [ 3 , 31 , 32 , 36 ] as in other tumors of the gastrointestinal tract including Barrett’s-associated esophageal adenocarcinoma, pancreatic and colorectal carcinoma [ 37 , 38 , 39 , 40 , 41 ]. Loss of expression of RPRM has been also reported in non-digestive tumors including breast, renal cell carcinoma, adrenocortical and pituitary tumors [ 33 , 34 , 35 , 42 , 43 ].…”
Section: Role Of the Rprm Gene Family In Humanmentioning
confidence: 99%